Nanogel do óleo essencial de Rosmarinus officinalis L. associado à fonoforese: efeito modulador sobre a lesão muscular induzida por veneno da serpente Bothrops moojeni - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2023)
The venom of B. moojeni (VBm) contains toxins that induce local toxic effects, triggering a severe inflammatory process, pain, hemorrhage, edema, and myonecrosis. Phonophoresis is a technique that uses therapeutic ultrasound (TUS) associated with an agent with pharmacological properties, optimizing drug delivery systems in nanoformulations. Rosmarinus officinalis is a plant with anti-inflammatory, analgesic, and antioxidant effects. Therefore, this study aimed to evaluate the modulatory effect of the application of R. officinalis nanogel associated with phonophoresis on VBm-induced muscle injury in Wistar rats. The chemical results demonstrated predominantly Limonene (5.08%), 1,8 Cineole (35.28%), and Camphor (46.92%) compounds. The nanoemulsion (NAE) exhibited stability with a mean drop diameter ranging from 213±2.1 (1st day) to 153.9±2.7 nm (30th day), with a polydispersity index ranging from 0.10±0.001 to 0.13±0.01. The nanogel was prepared from NAE in a carbopol hydrogel. A dose of 0.10 mg/kg of VBm was applied to induce inflammation in the gastrocnemius muscle. The evolution of edema volume showed that the groups treated with TUS (p<0.01), phonophoresis with Dexamethasone 0,5 mg/kg (p<0.001), and nanoemulsion 0,5 mg/kg (p<0.001) presented a significant anti-edematogenic effect. Moreover, they were able to reduce CK and myoglobin levels and the recruitment of inflammatory cells to the injury site. Histopathological findings reinforced the anti-inflammatory effect with decreased muscle damage and myonecrosis. Therefore, it is suggested that the modulatory effectiveness on the inflammatory process and muscle injury induced by VBm was demonstrated, both with TUS treatment and with phonophoresis associated with R. officinalis nanogel. Furthermore, the treatments were shown to attenuate tissue damage and enhance repair.
Keywords: Rosmarinus officinalis; Veneno de serpente; Fonoforese; Anti-inflamatório; Lesão muscular; Dano tecidual; CNPQ::CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; ODS 3 – Saúde e bem-estar